Mechanism for the origin of the Podolsky mass - Bonin, C. A.; Pimentel, B. M. [UNESP] (American Physical Society (APS), 2022)
In this paper we present an Abelian Higgs model in which the scalar field is nonminimally coupled with the Maxwell field. This model gives rise to the Bopp-Podolsky theory in the following way: for certain values of the coupling constants, when the U(1) symmetry is kept explicit, the resulting theory is the usual Maxwell theory for electromagnetism. On the other hand, in the hidden symmetry phase, the emerging theory for the electromagnetism is the Bopp-Podolsky theory.